2020
DOI: 10.5603/fm.a2020.0003
|View full text |Cite
|
Sign up to set email alerts
|

The potential gonadoprotective effects of grape seed extract against the histopathological alterations elicited in an animal model of cadmium-induced testicular toxicity

Abstract: Background: Grape seed extract (GSE) is a powerful antioxidant containing high levels of bioflavonoids, vitamin C and vitamin E. The aim of the work is to study the possible protective and ameliorative effects of grape seed extract in an animal model of cadmium (Cd)-induced testicular toxicity in rats. Materials and Methods:A thirty-day oral gavage study in adult male albino rats was performed using 32 animals, randomly divided into 4 equal groups; negative control, cadmium (5 mg/k/day), grape seed extract (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Mild congestion was present in the interstitial blood vessels. These findings are consistent with those reported in other studies (23,38,84,85) .…”
Section: Discussionsupporting
confidence: 94%
“…Mild congestion was present in the interstitial blood vessels. These findings are consistent with those reported in other studies (23,38,84,85) .…”
Section: Discussionsupporting
confidence: 94%
“…The scrotal testes showed +ve PCNA immunostained cells, mainly in the early stages of the spermatogenic cells and weak or absent PCNA immunostaining in the late stages. It was reported that the testicular tissues obtained from rats treated with cadmium had a harmful effect on the testis through its oxidative stress activity [27]. This was supported by Dutta et al [12] who proved that oxidative stress ameliorate the proliferation and induces apoptosis in the highly differentiated spermatogenic cells causing its degeneration in the order of; sperms, spermatids, spermatocytes then spermatogonia.…”
Section: Mean Area Per Cent Of Vimentin Immunostainingmentioning
confidence: 88%
“…Several studies have identified grape seed extract, grape seed pro-anthocyanidin extract, and grape juice concentrate as protective factors against cadmium toxicity. Grape seed extract and grape seed pro-anthocyanidin extract improved histopathological find-ings [132][133][134][135], increasing the diameter and normal SeT [132,135], testicular weight [132], and Johnsen's mean testicular biopsy score and decreasing the apoptotic index [135]. It was also observed to increase PCNA immunoreactivity [132] and total antioxidant status (TAS) [133] in the enzymes of the antioxidant defense system and genes associated with steroidogenesis and Ki-67 expression [134], and it decreased MDA levels [133,134] and the immunoreactivity of the apoptotic regulator Bax [134].…”
Section: Grapementioning
confidence: 97%
“…Grape seed extract and grape seed pro-anthocyanidin extract improved histopathological find-ings [132][133][134][135], increasing the diameter and normal SeT [132,135], testicular weight [132], and Johnsen's mean testicular biopsy score and decreasing the apoptotic index [135]. It was also observed to increase PCNA immunoreactivity [132] and total antioxidant status (TAS) [133] in the enzymes of the antioxidant defense system and genes associated with steroidogenesis and Ki-67 expression [134], and it decreased MDA levels [133,134] and the immunoreactivity of the apoptotic regulator Bax [134]. Grape juice concentrate treatment against cadmium toxicity demonstrated that co-administration restored the testis, epididymis, and ventral prostate weight [136] to normal levels, ameliorating tissue architecture [125,136,137], epididymis epithelium height (caput and cauda regions) [125] and improving sperm parameters such as production, counts, transit time [125], and morphology [136].…”
Section: Grapementioning
confidence: 97%